Digitalisasi Data Perpustakaan Dalam Proses Peminjaman dan Pengembalian Buku pada Perpustakaan Sekolah Islam ‘Uluwwul Himmah Medan. - Widiarti Rista Maya; Purwadi Purwadi; Saniman Saniman; Elfitriani Elfitriani; Suardi Yakub (STMIK Triguna Dharma, 2021)
'Uluwwul Himmah Medan School is one of the schools and kindergartens in Medan where one of the supporting teaching and learning activities is the school library as a medium of science development for children in the school. At 'Uluwwul Himmah Medan School library management is still done manually, for that it takes a computerized system in managing library books both the process of borrowing and returning books. With the system that has been built, the process of managing library books both the process of borrowing and returning can be done quickly and appropriately.